Pembuatan Video Animasi 2D Prosedur Pengajuan Kredit Di Master Cash And Credit Elektronik Furniture Menggunakan Aplikasi Toonboom Harmony - Yunintiyas (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Abstract At this time, the medium of conveying information in the form of animated videos is important. Like 2D Animation which is widely used to provide information to the audience. In this study, 2D animation was developed to socialize the credit application procedure at Master Cash and Credit Elektronik Furniture. This 2D animation video can mainly be made using the main application, namely Toonboom Harmony 20 with the motto of research and development (R&D) and the ADDIE development model (Analysis), Design ( Design ), Develop (Development), Implement (Implementation), and Evaluate (Evaluation). As well as the results of the 2D animated video, the credit application procedure at Master Cash and Credit Elektronik Furniture is divided into the audience to get a value of interest in seeing the video and is easy to understand by the audience. Keywords— 2D Animation, Harmony Toonboom 20, R&D, ADDIE Model